A multidisciplinary process for integrated rotorcraft design - Weiand, P.; Schwinn, D.; Schmid, M.; Buchwald, M. (My University, 2017)
This paper presents the activities of the German Aerospace Center (DLR) on integrated rotorcraft design. The process and design environment presented here are the results of two DLR internal projects carried out by the Institute of Flight Systems, the Institute of Aerodynamics and Flow Technology and the Institute of Structures and Design. The fundamental features of this process are distributed computation on the servers of the different institutes, analysis tools with increasing physical fidelity along the progress of the design process and a high modularity inside the software framework. The tools cover the phases of conceptual and largely preliminary design. The design process is initialized by a statistical concept study, providing the initial configuration for the following sizing and optimization task. The methods of the tools applied range from blade element theory over vortex panel theory, to finite element methods for structural sizing. This design toolbox is the foundation necessary for the DLR to tackle upcoming research tasks dealing with future unconventional rotorcraft configurations.